The plant Pontin and Reptin homologues, RuvBL1 and RuvBL2a, colocalize with TERT and TRB proteins in vivo, and participate in telomerase biogenesis. (9th April 2019) - Schořová, Šárka; Fajkus, Jiří; Záveská Drábková, Lenka; Honys, David; Schrumpfová, Petra Procházková
Summary: Telomerase maturation and recruitment to telomeres is regulated by several telomerase‐ and telomere‐associated proteins. Among a number of proteins, human Pontin and Reptin play critical roles in telomerase biogenesis. Here we characterized plant orthologues of Pontin and Reptin, RuvBL1 and RuvBL2a, respectively, and show association of Arabidopsis thaliana RuvBL1 (AtRuvBL1) with the catalytic subunit of telomerase (AtTERT) in the nucleolus in vivo . In contrast to mammals, interactions between AtTERT and AtRuvBL proteins in A. thaliana are not direct and they are rather mediated by one of the Arabidopsis thaliana Telomere Repeat Binding (AtTRB) proteins. We further show that plant orthologue of dyskerin, named AtCBF5, is indirectly associated with AtTRB proteins but not with the AtRuvBL proteins in the plant nucleus/nucleolus, and interacts with the Protection of telomere 1 (AtPOT1a) in the nucleolus or cytoplasmic foci. Our genome‐wide phylogenetic analyses identify orthologues in RuvBL protein family within the plant kingdom. Dysfunction of AtRuvBL genes in heterozygous T‐DNA insertion A. thaliana mutants results in reduced telomerase activity and indicate the involvement of AtRuvBL in plant telomerase biogenesis. Significance Statement: Plant orthologues of Pontin and Reptin, AtRuvBL1 and AtRuvBL2a, are associated together with AtTERT, AtTRB, AtPOT1a and plant dyskerin in the nucleolus. Reduced telomerase activity in heterozygous AtRuvBL plants indicates the involvement of AtRuvBL proteins in plant telomerase biogenesis.